Bioavailability-based environmental quality standards for metals under the water framework directive - Durjava, Mojca (Acta hydrotechnica, 2023)
Metals are naturally present in surface waters. By considering the bioavailability of a metal in an aquatic environment, we can more precisely predict the effect of a selected metal on aquatic organisms. This enables us to make a more reliable assessment of the compliance of the metal's concentration in inland surface waters with the environmental quality standard for that metal. In addition to complex-forming inorganic and organic ligands, the bioavailability of metals in water is also influenced by physicochemical conditions in the water. Metals occur in different concentrations and in different forms in aquatic environments. This is referred to as metal speciation. The bioavailability of a metal in water depends mainly on its speciation. Normally, a dissolved free metal ion is more bioavailable than a metal ion bound in a complex. The risks posed by given metals to aquatic environments are addressed under EU legislation in the Water Framework Directive (Council of the European Union, 2000) (WFD). The WFD’s purpose is to direct Member States to protect and improve the status of all water bodies throughout the European Union. Directive 2013/39/EC (Council of the European Union, 2013), which refers to priority substances as regards water policy, supplements the WFD and the Directive on environmental quality standards (Council of the European Union, 2008). For nickel and lead, Directive 2013/39/EC sets the annual average environmental quality standards (AA-EQS) for inland surface waters, which refer to biologically available concentrations of metals (AA-EQSbioavailable). In this way, uniform environmental quality standards for the entire European Union are determined for metals, allowing for a compliance assessment of metals for surface waters. In the article, we have presented an analysis of inland surface water monitoring data for nickel and lead, examining how the introduction of AA-EQSbioavailable affects the consistency of monitoring data for these metals. We used monitoring data from 2018 to 2021. To calculate bioavailable concentrations for nickel and lead, we used the bioavailability assessment model bio-met bioavailability tool v.2.3 (Bio-met, 2017). Additionally, for lead, we used equations (1), (2), and (3) to calculate the bioavailable concentration (European Commission, 2019). Based on the analysis conducted, we recommend the utilization of the bio-met model instead of the equations for calculating the concentration of bioavailable lead in the context of the annual compliance assessment of inland surface water monitoring data carried out by ARSO. Using the mentioned bioavailability assessment model, we have provided an upgrade in the methods used to assess metal’s concentration compliance with the EQS for that metal for surface waters. As a result, the requirements of Directive 2013/39/EC relating to biologically available concentrations of metals could be transferred to the Slovenian legal system.
Keywords: bioavailability of metals; biorazpoložljivost kovin; environmental quality standards; monitoring; okoljski standardi kakovosti; površinske vode; surface waters; Vodna direktiva; Water Framework Directive